2012
DOI: 10.1002/ijc.27575
|View full text |Cite
|
Sign up to set email alerts
|

Runt‐related transcription factor 3 reverses epithelial–mesenchymal transition in hepatocellular carcinoma

Abstract: Loss or decreased expression of runt-related transcription factor 3 (RUNX3), a tumor suppressor gene involved in gastric and other cancers, has been frequently observed in hepatocellular carcinoma (HCC). The objective of this study was to identify the regulatory mechanism of the epithelial-mesenchymal transition (EMT) by RUNX3 in HCC. Human HCC cell lines, Hep3B, Huh7, HLF and SK-Hep1, were divided into low-and high-EMT lines, based on their expression of TWIST1 and SNAI2, and were used in this in vitro study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…Tanaka et al . 35 also found that RUNX3 reversed the EMT in hepatocellular carcinoma, but the mechanism underlying RUNX3 action is different in gastric cancer cells. Tanaka et al .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Tanaka et al . 35 also found that RUNX3 reversed the EMT in hepatocellular carcinoma, but the mechanism underlying RUNX3 action is different in gastric cancer cells. Tanaka et al .…”
Section: Discussionmentioning
confidence: 95%
“…Tanaka et al . 35 showed that ectopic RUNX3 protein expression induced E-cadherin expression and suppressed vimentin expression in hepatocellular carcinoma cells with low EMT. However, in our study, RUNX3 did not induce E-cadherin in human gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…A role in EMT has also been described in cervical cancer, where JAG1 expression correlates with the rapid induction of phosphoinositol-3-kinase (PI3K)-mediated EMT (67); in hepatocellular carcinoma where it is repressed by the tumor-suppressor RUNX3 (68); and in treatment-resistant pancreatic cancer cells, where the JAG1-Notch2 axis controls several EMT transcription factors such as SNAIL, SLUG, and ZEB1 (69). Pro-invasive, migratory, and metastatic function has been also demonstrated for prostate cancer, where high JAG1 expression has been clinically linked to metastasis development and regulation of migration/invasion via NF-κB (70, 71), and for colon cancer, where it mediates APEX1 pro-tumorigenic functions and induces the metastasis markers MMP-2 and MMP-9 (72, 73).…”
Section: Jag1 Involvement In Cancermentioning
confidence: 99%
“…RUNX3 is a potential tumor suppressor gene for HCC, as the decreased mRNA expression of RUNX3 was observed in 50–92% of HCC cases (31,32). The significance of decreased expression of RUNX3 is related to dysfunction of cell cycle regulation, decrement of apoptosis (33,34), enhancement of angiogenesis, and the development of epithelial-mesenchymal transition (35). …”
Section: Molecular Alterations In Human Hccmentioning
confidence: 99%